Approaches to linguistic identity in the traditional Palestinian song - Al-Zeinati, Enas (Al-Adab Journal, 2024)
The Palestinian folklore is rich in vocabulary, styles and structures that reflect its national identity, and reveal the Palestinian personality and its features resulting from the impact of the occupation and the accompanying suffering, resistance and displacement, so this research came with the aim of highlighting the impact of language in drawing the features of the Palestinian national identity through the popular heritage song. The importance of the research stems from his discussion of the linguistic dimension in the Palestinian folk heritage song, and his analysis of the elements of the Palestinian identity in the traditional song, especially since this topic did not receive an independent study that reveals the linguistic dimension in the heritage song and linking it to the Palestinian national identity, and this study will be a tributary to the Arab library on this subject. In the research, I followed the descriptive and analytical approach, by monitoring the linguistic manifestations in the Palestinian heritage song, classifying the manifestations of the role of language in shaping the Palestinian identity by returning to different models of Palestinian folk songs, and then analyzing the models at the level of vocabulary and structures. I divided this study into two sections: theoretical, and applied, and devoted the theoretical section to concepts, terminology and theoretical knowledge related to the Palestinian national identity and the surrounding problems under the Israeli occupation, while the applied section was devoted to the statement of linguistic elements that contribute to drawing the features of national identity through selected models of Palestinian heritage songs. It reached a set of results, the most important of which are: that Palestinian folk songs involve linguistic manifestations of the identity of the Palestinian people, because they reflect their struggle with the occupier, and this was reflected in the vocabulary used that indicates the Palestinian environment, in addition to the Palestinian people’s continuous endeavor to preserve the national identity, and this was evident in the sentences, methods and structures used in them, which are conclusive evidence of the Palestinians’ desire to preserve their national identity, and they have harnessed the song as a tool for preserving identity.